Of forests and fields : Mexican labor in the Pacific Northwest - Sifuentez, Mario Jimenez, 1979- (New Brunswick, New Jersey : Rutgers University Press, 2016)
"Of Forest and Fields tells the story of the ethnic Mexicans that toiled in the fields, canneries, packing sheds, and forests who helped turn the Pacific Northwest into one of the most productive agricultural regions in the country. The book explores the struggle of Braceros, Tejanos, and Mexican immigrants, to contest their exploitation in various ways. The history of their resistance culminated in the creation of one of the most important farm worker's unions in the country, the Pineros y Campesinos Unidos Noreste (PCUN)"--Provided by publisher
Many miles from home : the bracero program in the Pacific Northwest -- Los Tejanos : the Texas-Mexican diaspora in Oregon -- The genesis of the Willamette Valley Immigration Project -- Whip that hoedad in the ground : undocumented workers in the national forests -- "Now I can hold my own with anybody" : IRCA, immigrant organizing, and the Pineros y Campesinos Unidos Noroeste (PCUN) -- Huelga! : PCUN and organizing farm workers in the Willamette Valley -- Epilogue: La lucha sigue.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: PCUN -- History; PCUN; Migrant agricultural laborers -- Northwest, Pacific -- History; Foreign workers, Mexican -- Northwest, Pacific -- History; Mexican Americans -- Northwest, Pacific -- History; Mexicans -- Northwest, Pacific -- History; Immigrants -- Northwest, Pacific -- History; Working class -- Northwest, Pacific -- History; Agricultural laborers -- Labor unions -- Northwest, Pacific -- History; Northwest, Pacific -- Economic conditions; Northwest, Pacific -- Ethnic relations; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; Agricultural laborers -- Labor unions; Economic history; Ethnic relations; Foreign workers, Mexican; Immigrants; Mexican Americans; Mexicans; Migrant agricultural laborers; Working class; Pacific Northwest; History